A Study on The Water Quality Assessment of The Renchong River at Muar, Johor - Lim Say Jing; Roslinda Ali; Nor Hazren Abdul Hamid (Progress in Engineering Application and Technology, 2022)
This study is carried out to determine the water quality of the Renchong River based on the WQI parameters. The land activities near the Renchong River were determined through Google Earth Pro and site visit. A total of 4 sampling stations are selected along the Renchong River, namely Station 1 or known as the Kundang Ulu Jetty Station, Station 2 or known as Pasar Gersik Station, Station 3 or known as Sungai Renchong Jetty Station and Station 4 or also known as Paya Limpah Station. The water sampling was carried out once a week for one month during both dry and rainy days. The samples were tested for the WQI parameters namely: i) Biochemical Oxygen Demand (BOD), ii) Chemical Oxygen Demand (COD), iii) Dissolved Oxygen (DO), iv) pH, v) Ammoniacal Nitrogen (NH3-N), and xi) Total Suspended Solid (TSS). Subsequently, the WQI index was calculated for all the four stations. In general, in terms of the WQI parameters, it can be said that with the exception of NH3-N, the water quality in all 4 stations were in the acceptable range for freshwater aquaculture. Lastly, the WQI results showed that the Station 3 which is the Sungai Renchong Jetty is the cleanest compared to other stations with water quality range between Class I and Class II.